Analisa Korelasi Rasio Arus Kas Dengan Financial Distress (Studi Kasus pada Perusahaan Telekomunikasi di Indonesia) - Sri Suharti (Media Nusantara, 2021)
Cash flow ratio analysis is useful for detecting financial distress, which occurs as a result of a company having negative cash flow so that it has difficulty meeting its obligations. This study aims to determine the relationship between cash flow ratios and financial distress in telecommunications companies in Indonesia. Research methodology that was used is descriptive study that utilize a quantitative approach. Sources of data are obtained from secondary data, with data processing methodolgy using the Spearman correlation formula and SPPS version 20.0. The results showed that the cash liability ratio, cash need coverage and asset efficiency ratio, and cash to debt ratio had a positive and significant correlation to financial distress as measured by the interest coverage ratio. This means that when the cash flow ratio increases, the level of financial distress will decrease. The positive cash flow ratio is caused by an increase in company cash receipts, especially from operational activities, which have an impact on increasing the company’s ability to pay its debts.